2018
DOI: 10.1111/2041-210x.12966
|View full text |Cite
|
Sign up to set email alerts
|

Community level lipid profiling of consumers as a tool for soil food web diagnostics

Abstract: Knowledge on food web structure and function provides important information on trophic relationships, energy flux, and ecosystem response to environmental changes. The tracing of trophic marker fatty acids (FAs) to assign predator–prey interactions is well established in food web research. However, the application on the level of entire consumer communities has not been performed yet. Here, we demonstrate that lipid pattern analysis of entire consumer assemblages can provide a first‐line assessment for food we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Proportions of EPA in total fatty acids reported are 3.5% for free-living soil nematodes (Kühn et al, 2018) and up to 17.4% for yeast feed Collembola (Chamberlain and Black, 2005). In particular, earthworms (their body, gut and burrow lining) are a rich source for LC-ω3PUFA, with EPA being 7.5 times higher than in bulk soil (Sampredo et al, 2006).…”
Section: ω3pufa-aquatic Vs Terrestrial Food Webs and Interlinksmentioning
confidence: 98%
“…Proportions of EPA in total fatty acids reported are 3.5% for free-living soil nematodes (Kühn et al, 2018) and up to 17.4% for yeast feed Collembola (Chamberlain and Black, 2005). In particular, earthworms (their body, gut and burrow lining) are a rich source for LC-ω3PUFA, with EPA being 7.5 times higher than in bulk soil (Sampredo et al, 2006).…”
Section: ω3pufa-aquatic Vs Terrestrial Food Webs and Interlinksmentioning
confidence: 98%
“…For soil food web, it has been shown that fatty acids (FAs) are transferred from microorganisms to microbivorous invertebrates to higher order consumers (Chamberlain et al, 2005;Ruess et al, 2002;Ruess, Schütz, et al, 2005;Ruess, Tiunov, et al, 2005) as well as from microorganisms and plants to detritivores and their predators (Pollierer, Scheu, & Haubert, 2010). Thus, lipid profiles of consumers may serve as tool for soil food web diagnostics (Kühn et al, 2018). To-date, however, virtually no studies investigated lipid profiles of soil fauna including both meso-and macrofauna in the same community.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were mostly qualitative or semiquantitative, considering fatty acid relative abundance instead of absolute values. As a major component in all organisms, lipids allow the following of carbon flux across trophic levels [8] or to uncover shifts in structure and resources of entire food webs [9]. Therefore, in an ecological context the development of quantitative approaches, i.e.…”
Section: Introductionmentioning
confidence: 99%